School Physical Safety and Social Relationships as Correlates of Teacher Productivity in Public Secondary Schools in Akwa-Ibom State of Nigeria (Global Journal of Human-Social Science, 2020)
The study examined school physical safety and social relationships as correlates of teacher productivity in public secondary schools in Akwa-Ibom State of Nigeria. Two (2) research questions and 2 hypotheses guided the study. The design of the study was correlational, with the population as the 268 public secondary schools in the state. These schools have 268 principals, from which 203 (76%) were selected as sample, using the simple random sampling technique. The instruments of the study were the validated 18 item Physical Safety and Social Relationship Scale and the 11 item Teacher Productivity Scale (TPS), designed by the researchers with reliabilities of 0.86 and 0.88, respectively. Pearson Product Moment Correlation Co-efficient was used in answering the research questions while the Pearson r.values were converted to p.values and used in testing the hypotheses, at 0.05 level of significance. The results of the study show positive high correlation between school physical safety and social environment and teacher productivity. The findings also establishes significant correlation between school physical safety, social relationships and teacher productivity.
Keywords: school physical safety; social relationships; teacher productivity